(untitled) (Annals of Medical Research, 2024)
Aim: Intermediate altitude (IA) is a risk factor for the development of cardiovascular disease due to low oxygen levels. At IA, adaptive mechanisms develop both in the pulmonary and systemic circulatory systems from an early period. The effects of IA on atrial functions were investigated in the present study by using speckle-tracking echocardiography. Materials and Methods: The present study was on the subjects living at IA for 1 year. The effects of IA on atrial functions were investigated by comparing the baseline and first-year echocardiographic data of the subjects. Results: A total of 67 subjects were included in this study. The mean age of the patients was 44.5 ± 6.2 years, and 62% of them were males. At the end of the first year, the left atrial (LA) conduit strain (p:0.011), reservoir strain (p:0.032), and contractile strain (p:0.037) rates were found to be significantly higher, whereas the left atrial volume index (p:0.005) was determined to be lower. Conclusion: IA leads to the development of adaptive mechanisms in the cardiovascular system, and the maintenance of tissue oxygenation is not affected by these mechanisms. These adaptive changes can be detected in LA structure and functions from the first year in individuals living at high altitudes.